Dermoid Cyst of the Pancreas - Campani, Daniela; Gallippi, Grazia; Granai, Monnalisa; De Lio, Nelide; Boggi, Ugo (JOP. Journal of the Pancreas, 2012)
Context Cystic lesions of the pancreas constitute a wide spectrum of entities ranging from non-neoplastic to malignant neoplastic lesions. Dermoid cysts (cystic teratoma) are uncommon benign, well-differentiated germ cell lesions. Teratomas can be divided into mature and immature subtypes. Mature cystic teratoma is commonly found in the ovary. The pancreas is extremely rare as primary site. Case report A 59-year-old asymptomatic man in a follow-up for occupational exposure to asbestos was submitted to chest computed tomography (CT): incidentally evidenced a left sub-diaphragmatic expansive lesion. Physical examination and laboratory tests were normal. Abdominal ultrasound (US) evidenced a partial cystic mass located in the anterior para-renal space in continuity with the pancreatic tail. The duct of Wirsung was regular. Abdominal CT and magnetic resonance imaging (MRI) showed an 80×60×40 mm hypodense lesion in the pancreatic tail, partly solid and partly fluid. No signs of non resectability or metastases were found. The patient was submitted to robotic-assisted surgery. The cyst originated from the pancreatic tail and only a small portion of the pancreatic tail was removed. The post-operative course was regular and the patient was discharged on post-operative day eight. Macroscopic examination displayed a cyst with smooth walls containing sebaceous material. Histology showed an intrapancreatic cyst lined with typical, focally keratinized, stratified squamous epithelium with sebaceous glands in the underlying stroma, surrounded by intense lymphoid infiltrate with germinal centers. The diagnosis was dermoid cyst of the pancreas. Conclusion Clinical presentation of pancreatic dermoid cyst is not specific and occurs preferably in younger ages. Symptoms range from an asymptomatic palpable mass to obstructive jaundice, abdominal pain, back pain, vomiting, anorexia, weight loss; some cases are diagnosed occasionally. Dermoid cyst of the pancreas is a true cyst. Differential diagnosis of lesions that mimic cystic neoplasm of the pancreas is still difficult. US, CT and MRI may be helpful, but there are no pathognomonic data for preoperative identification. The robotic surgery allows to perform challenging pancreatic resections.